Pengaruh Penggunaan Media Roda Putar terhadap Kemampuan Mengenal Huruf Vokal dan Konsonan Peserta Didik Kelas I SDN 8 Oheo Kab. Konawe Utara - Nurinsana, St.; Djafar, Hamsiah; Rosdiana (Primer Edukasi Journal, 2024)
This study aims to determine: (1) The ability to recognize vowels and consonants of students before using the rotary wheel at SDN 8 Oheo, North Konawe Regency, (2) The ability to recognize vowels and consonants after using the rotary wheel at SDN 8 Oheo, Konawe Regency North, and (3) Is there a difference after using the rotary wheel media in class I SDN 8 Oheo, North Konawe Regency. The results of the analysis show that the average value of learning outcomes before using the rotary wheel media is 40.86 in the low category. While the average value of learning outcomes after being taught using a rotary wheel media of 74.78 is in the high category. The results of the hypothesis test show that there are differences in learning outcomes before and after being taught using the rotary wheel media, when seen from the average post-test learning outcomes is greater than the pre-test scores. So the use of a rotary wheel media can affect the ability to recognize vowels and consonants of students in class I SDN 8 Oheo, North Konawe Regency.